Aplikasi Kahoot sebagai Salah Satu Media Penilaian Interaktif Grammar Kelas 10 SMK Trunojoyo Jember - Samsudin, Asep; Wardani, Peni Arianita; Rachman, Nur Afni; Farhan, Muhamad; Binarkaheni, Suyik (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
This community service activity aimed to improve students’ English grammar competence through the implementation of a game-based learning approach using Kahoot! at SMK Trunojoyo Jember. The program was designed based on initial observations indicating that Grade 10 students experienced difficulties in understanding basic grammar structures, particularly tenses, subject-verb agreement, and sentence construction. In addition, students showed low learning motivation and limited engagement during conventional classroom instruction. The intervention was conducted through a structured process consisting of needs analysis, pre-assessment, training sessions, and post-assessment over nine meetings. Kahoot! was utilized as an interactive learning and assessment platform to create a more engaging and competitive learning environment. The results showed a significant improvement in students’ grammar understanding, accuracy in answering questions, response speed, and overall participation. Moreover, students demonstrated higher motivation and more active involvement during learning activities. The findings suggest that the integration of digital game-based learning tools such as Kahoot! can effectively enhance both cognitive and affective aspects of language learning in vocational school contexts. This approach also supports the development of a more interactive, student-centered, and technology-integrated learning environment.